PENGEMBANGAN MODEL PEMBELAJARAN BERBASIS PROYEK LINGKUNGAN UNTUK MENINGKATKAN LITERASI EKOLOGI MAHASISWA - Faediyah, Faediyah; Anjelli, Susan; Fasihaturrohmah, Sifa (CV. Kalimasada Group, 2024)
Ecological literacy is the ability to understand ecological principles, recognize environmental issues, and take responsible action towards the environment. This learning model is designed to actively involve students in projects related to the environment, so that they can gain hands-on experience and build a deeper understanding of ecological concepts. This research aims to develop an ecological environmental project-based learning model that is effective in increasing student literacy. The research method used is qualitative with a descriptive approach. Data collection techniques are carried out through observation, interviews and documentation. It is hoped that the results of this research can contribute to the development of innovative and effective ecological learning models to increase student literacy, as well as support efforts to preserve the environment. The implication of the results of this research is the need to implement environmental project-based learning models in various study programs in higher education to increase students' ecological literacy and encourage them to become agents of change in preserving the environment.